Isolation, structural characterization and neurotrophic activity of a polysaccharide from Phellinus ribis. (20th August 2015) - Liu, Yuhong; Liu, Chunhui; Jiang, Haiqiang; Zhou, Honglei; Li, Pingli; Wang, Fengshan
Highlights: A new polysaccharide named PRG was obtained from Phellinus ribis . Monosaccharide composition analysis confirmed that PRG consisted of glucose only. PRG was defined to be a (1→3), (1→6)-β-D-glucan. PRG promoted the neurite outgrowth of the nerve growth factor-stimulated PC12 cells. Abstract: A new polysaccharide named PRG was isolated from the fruiting bodies of Phellinus ribis by hot water extraction, ethanol precipitation, anion-exchange and gel-filtration chromatography. PRG was homogeneous, with a molecular weight of 5.16 × 10 3 Da, as determined by high-performance size-exclusion chromatography–multiangle laser light scattering analysis. Its structural characteristics were investigated and elucidated by methylation analysis, partial acid hydrolysis, gas–liquid chromatography mass spectrometry, Fourier transform infrared and nuclear magnetic resonance spectroscopy. Based on obtained data, PRG was found to be a β-d -glucan containing a (1 → 3)-linked backbone, with a branch of two (1 → 6)-linked and one terminal glucoses substituting at the C-6 position every three residues, along the main chain. PRG exhibited neurotrophic activity, which significantly promoted the neurite outgrowth of the nerve growth factor-stimulated PC12 cells, suggesting that it might be a potential candidate for the treatment of neurodegenerative diseases.